Isolation and Identification of Oral Bacteria and Characterization for Bacteriocin Production and Antimicrobial Sensitivity - Rahman, Monzilur; Islam, Md Nahidul; Islam, Muhammad Nurul; Hossain, Mohammad Shahnoor (Dhaka University Journal of Pharmaceutical Sciences, 2015)
Oral bacteria play an important role in body homeostasis and the bacterial genus Streptococcus is the dominant microflora commonly found in oral bacterial community. Their ability to establish biofilm lifestyle in the oral cavity by outcompeting other bacteria has been attributed to the production of bacteriocin along with other strategies. The goal of the present study was to isolate and identify oral bacteria and characterize their ability to produce bacteriocin against other oral bacteria as well as their sensitivity to common antibiotics. We have employed deferred antagonism bacteriocin assay for bacteriocin production and disk diffusion assay for antibiotic susceptibility testing. We identified eight bacterial strains belonging to the genera Streptococcus and Enterococcus based on colony morphology, biochemical assays, 16S rDNA sequence analysis, and species-specific PCR. Antibiotic susceptibility assay indicated that some of the strains are resistant to one or more antibiotics. Our study also revealed that the isolated strains are capable of producing one or more bacteriocins against other oral bacteria. Further molecular and biochemical studies are required to understand the nature of observed bacteriocin. Dhaka Univ. J. Pharm. Sci. 14(1): 103-109, 2015 (June)